Modeling of silicon solar cells performances by MATLAB - ABDELBAKI , Cherouana; REBIHA , Labbani (International Journal of Computational and Experimental Science and Engineering, 2015)
In this work, the programming tool MATLAB was used to predict the performances of single-crystal silicon solar cells. Two particular structures were studied, namely the conventional cell of N+P type and the cell with a Back surface field (BSF) layer of the N+PP+ type. The parameters of these cells (the tension of open circuit, the current of short circuit and internal quantum efficiency (IQE)) were estimated with a good accuracy. Back surface field silicon (i.e. N+PP+) structures were found to have better characteristics than the conventional solar cells. We noticed that the effective recombination velocity of the minority carriers could be minimized by simple optimization of the doping concentration in the back layer. The results were in agreement with literature.